QR Code-Based Educational Media as a Strategy to Improve Nursing Students’ Knowledge of Pain Management - Surya, Surya Prihatini; Aulya, Aulya Kartini Dg Karra; Dewi Sartika, Dewi Sartika MS; Nurafni Suid, Nurafni Suid; Kurniawati, Kurniawati (Bantayang Omni Cendekia, 2025)
Background: Pain management is one of the essential competencies that nursing students should possess. However, knowledge in this area remains suboptimal. One of the media that can be utilized to enhance education is the Quick Response (QR) Code, which enables quick, flexible, and repeated access to materials, thereby potentially improving students’ understanding of pain management. Objective: This study aimed to determine the effectiveness of QR Code–based educational media in improving nursing students’ knowledge of pain management Methods: This study employed a pre-experimental design with a pretest–posttest one-group approach. The sampling technique used was a total sampling technique, involving 25 respondents. Results: The findings indicated that the effectiveness of QR Code–based educational media in improving nursing students’ knowledge of pain management was mostly in the good category. However, despite having good knowledge, students still need improvement in practical skills and attitudes. Conclusion: Nursing students’ knowledge of pain management after receiving education through QR Code–based media falls into the good category. However, several aspects still need improvement, such as practical skills and professional attitudes, through training such as simulations and practice integrated into the nursing curriculum.